Introduction to Issues and Technology in Water Contaminants - Puteh, Mohd Hafiz; Abdullah, Noorul Hudai (Penerbit UTM Press, 2020)
About 70% of the earth’s surface is covered with water. Although the quantity of water on earth is vast, most of this does not fit for direct human consumption, particularly the saline water. The most accessible source of fresh water for human consumption is the surface water, including rivers and lakes, which consist of about 0.3% of the total fresh water volume on earth (Gleick, 1996). Unfortunately, the access to clean fresh water is inadequate in many parts of the world. This is largely due to the deterioration of raw water quality and the threat of water contaminants.